AgDataHub-Mali: Updates on Dashboard Enhancements - Annaiah, Akshatha (Accelerating Impacts of CGIAR Climate Research for Africa, 2024)
This report provides an overview of recent enhancements made to the AgDataHub-Mali digital platform, which integrates agro-meteorological, agricultural, soil, and satellite data to support climate-resilient farming. Developed under the AICCRA-Mali initiative and hosted by Mali-Météo, the platform's updated dashboard offers improved access to real-time and historical data, tailored digital advisories, and actionable insights for a range of users including policymakers, extension services, and smallholder farmers. These updates aim to strengthen decision-making capacity, improve food security, and build resilience to climate change in Mali's agriculture sector.